ASSOCIATIONS BETWEEN CLINICAL COURSE, LEFT VENTRICULAR HYPERTROPHY SEVERITY AND ACE GENE I/D POLYMORPHISM IN PATIENTS WITH HYPERTROPHIC CARDIOMYOPATHY AND HYPERTENSIVE HEART - M. D. Smirnova; T. V. Fofanova; Z. B. Khasanova; A. G. Ovchinnikov; F. T. Ageev; A. Yu. Postnov (Российский кардиологический журнал)
The manifold studies on ACE gene impact on left ventricular hypertrophy (LVH) development in hypertrophic cardiomyopathy (HCMP) and arterial hypertension (AH) have provided too contradictory results to clarify the association between ACE gene I/D polymorphism and cardiovascular pathology in these nosologic forms. The study aimed to analyse the associations between clinical course, LVH severity, and ACE gene polymorphism among HCMP and AH patients. In total, 35 HCMP patients and 33 individuals with long AH duration and LVH were examined. ACE gene I/D polymorphism was studied by PCR method. Electrocardiography (ECG) and echocardiography (EchoCG) were also performed. In HCMP, ID type of ACE gene was associated with more severe ECG signs of LVH (voltage, ST-T changes), comparing to DD type. II Type was linked to greater myocardial mass, interventricular septum thickness, and left atrium dilatation, comparing to DD type. II allele was regarded as a risk allele. In AH and LVH, ACE gene ID type was associated with a tendency towards greater interventricular septum thickness, while II allele was very rare (5,4%) and linked to LVH absence. No relations to clinical course and ECG changes were observed.